Business Writing For Everyone - Cruthers, Arley (Open textbook library., 2024)
Business Writing For Everyone is an inclusive guide to writing in the workplace. The book takes a process-oriented, storytelling approach to composition: focusing less on genre and more on the decisions that effective business communicators make. Business Writing For Everyone also contains interactive H5P activities for students to test their learning, and activities for further reflection that instructors can use in the classroom or assign as homework.